Use of Head Computed Tomography (CT) in the Pediatric Emergency Department in Evaluation of Children With New-Onset Afebrile Seizure. (October 2018) - Veerapandiyan, Aravindhan; Aravindhan, Akilandeswari; Takahashi, James Huynh; Segal, Devorah; Pecor, Keith; Ming, Xue
Objective: Cranial computed tomography (CT) is not recommended in the routine evaluation of children with first afebrile seizure due to its low yield. The objective was to assess the current practice in our pediatric emergency department regarding the use of head CT in children with first afebrile seizure and to identify the factors that lead to ordering a head CT. Methods: Medical records of patients between 1 month and 18 years old evaluated at our emergency department for presentation of first afebrile seizure between 2010 and 2014 were retrospectively reviewed. Data extracted include age, gender, seizure type, single or multiple seizures at presentation, seizure duration, predisposing conditions to seizures (ie, history of developmental delay), and whether a head CT was performed. Contingency tables with chi-square analyses were used to determine which variables were associated with increased use of head CT. Results: Of 155 patients (88M/67F) included in the study, 72 (46.5%) underwent head CT and only 3 had clinically significant findings that did not require acute management. There were no differences in CT use by age, sex, seizure type, seizure number, seizure risk factors, or findings on physical examination. Head CT was performed more frequently in cases with seizures ≥5 minutes and unknown seizure duration ( P = .04). Conclusion: Despite existing evidence, the emergent head CT rate was high in our cohort. Children with seizure duration of ≥5 minutes or of unknown duration were more likely to undergo head CT in our emergency department.